Conceptualizing and measuring recreation safety climate. (August 2016) - Cheng, Tien-Ming; Chen, Mei-Tsun; Hong, Ci-Yao
Highlights: Extending safety climate research into recreation activities context. Utilizing the qualitative approach to explore recreation safety climate (RSC). Develop a set of tools to measure recreationists' perception of RSC. Contributing to the knowledge by expanding the understanding of safety climate on recreation activities. Abstract: Recreation safety is a central part of recreational activities. Establishing a recreation safety climate (RSC) can facilitate the measurement of safety practices at a place of recreation. The emphasis of this study is to conceptualize RSC and develop a set of tools to measure the degree of recreationist perception of the safety level in a recreation place. The study starts with in-depth interviews and content analysis to produce the initial questionnaire items. Exploratory factor analysis and confirmatory factor analysis are then applied to build reliable and valid measurement tools. The study results identified eight constructs to RSC: management commitment to safety, perception of recreation safety rules, fit between recreational environment and safety, safety training for recreationists, responsible managers, emergency facilities, caring, and altruistic safety behavior. Also identified were 27 measurement items to help recreation managers apply safety management practices.